Case report: Bullous pemphigoid associated with sintilimab therapy for pMMR/MSS colorectal cancer - Wang, Ting; Shao, Qianwen; Xiao, Chunmei; Liu, Lianke (Frontiers in Oncology, 2023)
Immunotherapy has become a very effective treatment for many cancers. It has a unique set of immune system-related adverse effects, collectively known as immune-related adverse events (irAEs). Skin toxicities are the most common irAEs, of which bullous pemphigoid, although rare, is potentially life-threatening and affects patients’ survival. In this article, we report the treatment of bullous pemphigoid caused by programmed cell death protein-1 (PD-1) in a case of proficient mismatch repair (pMMR)/microsatellite stable (MSS) colorectal cancer. No significant adverse effects were observed in the patient after methylprednisone was tapered to 4 mg twice a day. No new skin lesions occurred recently in the patient and the original skin lesions healed. In particular, the patient’s immunotherapy was not stopped and the best outcome was a partial remission of the disease, lasting for more than 8 months.